Impact of ICT in libraries/ Mohd Nazrull Afezie Nadzri - Nadzri, Mohd Nazrull Afezie (2012)
The revolutionary of the Information Communication Technology (ICT) and mobile/smartphone give the huge impact to the society. The libraries also are not exceptional in this revolution. Over relatively short periods of time, technological changes, such as the introduction of Web browsers, have had a major, and some would say revolutionary, impact on higher education as well as the boarder society.